“Mises en abyme” and satirical descriptions: “characters” of writing and writers in seventeenth-century England - Claire Labarbe (Etudes Epistémè)
This article demonstrates that the genre of seventeenth-century English “character-books” was highly self-reflexive. Authors theorized the act of writing by discussing the rules and complexities of literary composition in their prefaces and introductions. They also illustrated the process of writing in the body of their texts by representing diverse “characters” of writers. These were sometimes meant as a reflexion of the authors themselves, and their works and style were then presented as instances of artistic achievement. Conversely, hack writers practising other genres than that of character-writing were satirized along with their cheap poems, trite ballads, trivial diurnals, provocative libels or blasphemous pamphlets. The extraordinary development of cheap print during the Civil War was reflected in the evolution of “character-books”. Indeed authors of characters responded to the growing competition of pamphlets by satirizing cheaper forms of literature as artistically inferior. But the success of cheap print also meant that “characters” were increasingly published as pamphlets. By lampooning writers of “base” literary forms, authors of characters thus partly satirized themselves.